THEME IN SHAKESPEARE’S “KING LEAR” - NFN Mustafa (SAWERIGADING, 2010)
This paper examines concerning an aging pagan king of ancient Briton, seeks to divide his kingdom among his daughters and their suitors according to a test of how well they can express their love in words. The aim of this paper is to examine theme in Shakespeare’s "King Lear" in applying love value of Lear’s daughters to their father (King Lear). How Shakespeare develops this theme so that it can be alive and pleased by all readers of literary work as well as becoming one of the biggest in Shakespeare’s “tragedy” until now.  Shakespeare has treated all characters very successfully by making them play out their roles and make a complete dramatic unity. He keenly put human life in the whole process of his drama mainly by putting down love and conflict among those characters. Abstrak Makalah ini mengisahkan tentang seorang raja di Inggris Raya yang akan membagikan kekuasaannya kepada para ahli warisnya (ketiga putrinya) berdasarkan kadar cinta yang dimiliki untuk ayahnya dengan melakukan tes mengekspresikan cintanya kepada ayah dengan kata-kata cinta. Makalah ini bertujuan untuk meneliti tema “King Lear” dalam penerapan tentang kadar cinta putri-putri Lear kepada orang tuannya (Raja Lear). Bagaimanakah tema cerita yang ditampilkan oleh Shakespeare dalam mengembangkan cerita ini sehingga dapat hidup dan disenangi oleh para penikmat karya sastra dan juga menjadi salah satu karya terbesar drama tragedi Shakespeare hingga saat ini.  Shakespeare telah berhasil dengan baik dalam mengejawantahkan terhadap peran para pelaku cerita, dan penyusunan sebuah wacana drama yang lengkap. Ia dengan teliti meletakkan dasar hidup manusia dalam seluruh proses dramanya dengan menempatkan konflik dan cinta di antara para pelaku cerita.